Type-I PtS2/MoS2 van der Waals heterojunctions with tunable photovoltaic effects and high photosensitivity. Issue 43 (14th October 2022) - Zhang, Hui; Wang, Zihan; Chen, Jiawang; Tan, Chaoyang; Yin, Shiqi; Zhang, Hanlin; Wang, Shaotian; Qin, Qinggang; Li, Liang
Abstract : A high-performance photodetector based on type-I PtS2 /MoS2 van der Waals heterojunction is introduced. The photovoltaic effect and the photocurrent of this heterojunction can be effectively modulated by the negative gate voltage. Abstract : Recent advances in two-dimensional (2D) materials play an essential role in boosting modern electronics and optoelectronics. Thus far, transition metal dichalcogenides (TMDs) as emerging members of 2D materials, and the van der Waals heterostructures (vdWHs) based on TMDs have been extensively investigated owing to their prominent capabilities and unique crystal structures. In this work, an original vdWH composed of molybdenum disulfide (MoS2 ) and platinum disulfide (PtS2 ) was comprehensively studied as a field-effect transistor (FET) and photodetector. A gate-tunable rectifying behavior was obtained, stemming from the band design of PtS2 /MoS2 vdWH. Upon 685 nm laser illumination, it also exhibited a superior photodetection performance with a distinctly high photoresponsivity of 403 A W −1, a comparable detectivity of 1.07 × 10 11 Jones, and an excellent external quantum efficiency of 7.32 × 10 4 %. More importantly, fast rise (24 ms) and decay (21 ms) times were obtained under 685 nm light illumination attributed to the unilateral depletion region structure. Further, the photovoltaic effect and photocurrent of the heterojunction could be modulated by a back gate voltage. All these results indicated that such 2D-TMD-based vdWHs provide a new idea for realizing high-performance electronic and optoelectronic devices.